Two Populations of Mites (Tyrophagus putrescentiae) Differ in Response to Feeding on Feces-Containing Diets - Hubert, Jan; Nesvorna, Marta; Sopko, Bruno; Smrz, Jaroslav; Klimov, Pavel; Erban, Tomas (Frontiers in Microbiology, 2018)
Background:Tyrophagus putrescentiae is a ubiquitous mite species in soil, stored products and house dust and infests food and causes allergies in people. T. putrescentiae populations harbor different bacterial communities, including intracellular symbionts and gut bacteria. The spread of microorganisms via the fecal pellets of T. putrescentiae is a possibility that has not been studied in detail but may be an important means by which gut bacteria colonize subsequent generations of mites. Feces in soil may be a vector for the spread of microorganisms. Methods: Extracts from used mite culture medium (i.e., residual food, mite feces, and dead mite bodies) were used as a source of feces-inhabiting microorganisms as food for the mites. Two T. putrescentiae populations (L and P) were used for experiments, and they hosted the intracellular bacteria Cardinium and Wolbachia, respectively. The effects of the fecal fraction on respiration in a mite microcosm, mite nutrient contents, population growth and microbiome composition were evaluated. Results: Feces from the P population comprised more than 90% Bartonella-like sequences. Feces from the L population feces hosted Staphylococcus, Virgibacillus, Brevibacterium, Enterobacteriaceae, and Bacillus. The mites from the P population, but not the L population, exhibited increased bacterial respiration in the microcosms in comparison to no-mite controls. Both L- and P-feces extracts had an inhibitory effect on the respiration of the microcosms, indicating antagonistic interactions within feces-associated bacteria. The mite microbiomes were resistant to the acquisition of new bacterial species from the feces, but their bacterial profiles were affected. Feeding of P mites on P-feces-enriched diets resulted in an increase in Bartonella abundance from 6 to 20% of the total bacterial sequences and a decrease in Bacillus abundance. The population growth was fivefold accelerated on P-feces extracts in comparison to the control. Conclusion: The mite microbiome, to a certain extent, resists the acquisition of new bacteria when mites are fed on feces of the same species. However, a Bartonella-like bacteria-feces-enriched diet seems to be beneficial for mite populations with symbiotic Bartonella-like bacteria. Coprophagy on the feces of its own population may be a mechanism of bacterial acquisition in T. putrescentiae.